2001
DOI: 10.1590/s1519-69842001000400004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypoxia and recuperation on carbohydrate metabolism in pacu (Piaractus mesotamicus)

Abstract: A study of the hematological parameters, glycogen, glucose, and lactate, and the activity of malate and lactate dehydrogenases was carried out in blood and tissues of fishes submitted to two, four, and six hours of hypoxia and recuperation. Only after 4 h of hypoxia was there a drop in liver glucose. Alter 16 h, a drop in lactate and a rise in glucose in practically all tissues signaled a recuperation of the metabolism, probably due to ASR (aerial surface respiration). Lactate formed during hypoxia was canaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
(14 reference statements)
3
10
1
Order By: Relevance
“…This support the predominance of aerobic metabolism in all the tissues except muscle, agreeing with other studies carried out on fish (Childress & Somero 1979, Yang et al 1992, Panepucci et al 2000, Panepucci et al 2001, Treberg et al 2003 and most vertebrates (Hochachka & Somero 1973).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This support the predominance of aerobic metabolism in all the tissues except muscle, agreeing with other studies carried out on fish (Childress & Somero 1979, Yang et al 1992, Panepucci et al 2000, Panepucci et al 2001, Treberg et al 2003 and most vertebrates (Hochachka & Somero 1973).…”
Section: Discussionsupporting
confidence: 92%
“…It is important to highlight the elevated LDH activity found in M. gayi gayi liver, which does not agree with the typically low activity of this enzyme in this organ observed in other fish species (e.g., Panepucci et al 2001, Cooper et al 2002, and with the belief that this organ is considered a predominantly aerobic tissue with high blood irrigation (Hinton et al 2009). These high LDH levels could be an indication of metabolic failure of the liver (Orrego et al 2010) due to the exposure of M. gayi gayi to pollution sources (industrial waste and domestic sewage) associated with the Biobío river and the coastal zones of centralsouthern Chile (e.g., Parra et al 1993, Riveros et al 1996, Muñoz 2002, also demonstrated by other studies (Monteiro et al 2007, Orrego et al 2011.…”
Section: Discussionmentioning
confidence: 88%
“…This may be consistent with the primary function of liver in glucose export during hypoxia for metabolism by extra-hepatic tissues such as heart and brain, which are important in the maintenance of an organism's homeostasis (Panepucci et al 2001;Martínez et al 2011). …”
Section: Discussionsupporting
confidence: 76%
“…Although LDH plays a critical role in anaerobic metabolism, it is also involved in the process of gluconeogenesis by catalyzing the conversion of lactate into pyruvate, which can then be used for glucose production. Consequently, the role of higher LDH activity in livers from fish collected in the hypoxic Rwembaita Swamp may be in the clearance of blood lactate and the provision of glucose for metabolism by extra-hepatic tissues such as heart and brain, which are important in the maintenance of an organism's homeostasis [30-32]. …”
Section: Discussionmentioning
confidence: 99%